(untitled) (Al-Mansour Journal, 2022)
A sticky bomb is an explosive device, usually IED (Improvised Explosive Device), which can be affixed to a vehicle either by magnetism or an adhesive. Any person in our country has suffered from the effect of these devices, yet nothing can be done to avoid the threat only one has to inspect his car personally at each time he has to drive his vehicle, no tools are available for civilian and in an affordable price to detect a sticky bomb without risking a person’s own life. The existing methods are very expensive yet not available for civilians, further more it has a number of weakness points that we will discuss later, our proposed method is efficient, cheap, easy to implement and has no weakness point which may be exploited by terrorists, it depends on laser 3D scanning for the bottom of the vehicle to form a 3D initial model and store it into the systems memory, then when a person remotely activate the system it will rescan the surface for changes and tampers, if such change is found an alarm will be sounded reflecting the size of the change and locates the foreign body on the car’s bottom surface. This method can overcome the drawbacks of the existing methods and add a new level of robustness for sticky bomb detection techniques to save lives in our country.